The role of the National bank of the Kyrgyz Republic in the legal regulation of bank lending (Journal of actual problems of jurisprudence, 2019)
This article describes the powers and functions of the National Bank of the Kyrgyz Republic in the field of bank lending in the Kyrgyz Republic. It is noted that the National Bank and financial – credit organizations are one of the important components of the financial system of the state. The activities of financial and credit organizations are monitored and regulated by the National Bank in order to facilitate the solution of national tasks of the Kyrgyz Republic. The article discusses the subjects of banking legal relations, and also reveals the status of clients of financial and credit organizations, shareholders and depositors as subjects of civil legal relations. Also, the authorities and functions of the National Bank on the Civil Code of the Kyrgyz Republic, the Law of the Kyrgyz Republic of 7 May 2008 No. 78 “On the Protection of Bank Deposits (Deposits)”, the Law of the Kyrgyz Republic, the Law of the Kyrgyz Republic of 16 December 2016 No. 206 “On the National Bank of the Kyrgyz Republic Republic. The article also discusses the private and public powers of the National Bank, the functions of control and supervisionover the activities of financial and credit institutions.Key words: banking, bank lending, financial institutions, powers of the National Bank of the KyrgyzRepublic, banking regulation, control and supervision functions.